Mapping Dissertation-Writing Challenges Among Moroccan Doctoral Students: A Quantitative Descriptive Study - DARDOUR, Majid (International Journal of Language and Literary Studies, 2026)
Doctoral dissertation writing is a demanding academic process and a key component of research capacity development. Despite increased investment in higher education, doctoral completion remains a major concern in Morocco. This quantitative descriptive study examines the prevalence and severity of dissertation-writing challenges among Moroccan doctoral students. Data were collected through a questionnaire administered to 300 doctoral candidates enrolled in English studies across Moroccan universities and analyzed using descriptive statistics. The findings show that systemic and personal obstacles—particularly stress, anxiety, and time-management difficulties—represent the most severe challenges. Substantial difficulties were also reported in research planning and methodological rigor, especially research design and statistical analysis, as well as in critical academic writing and discussion chapter development. These findings highlight the need for targeted institutional interventions, including enhanced methodological training, academic writing support, psychological assistance, and improved supervisory practices to support timely doctoral completion and research productivity in Morocco.